ANTIULCER AND CYTOPROTECTIVE ACTION OF WEDELIA CALENDULACEA LESS - Hegde, D.A. (Medknow Publications & Media Pvt Ltd, 1994)
The gastric antiulcer and ulcer healing effect of the ethanolic and aqueous extracts of the dried leaves of Wedelia calendulacea. Less was found to be significant. The effect of the aqueous extract was observed to be more pronounced in comparison with that of the ethanolic extract.